The underlying causes of forest decline - Contreras Hermosilla, A. (Center for International Forestry Research, 2000)
Loggers, miners and rural communities all exploit forests in unsustainable ways in search of profits and means of subsistence. They are the primary actors in forest decline and their immediate motivations are the direct causes of deforestation and degradation. However, these motivations are determined, through complex causation chains, by deeper and much more fundamental forces: the underlying causes of deforestation. Effective action against forest decline requires an understanding of these underlying causes and their distant impacts on forests. Underlying causes originate in some of the most basic features of society, such as the distribution of economic and political power, attitudes towards corruption, population growth, flaws in the market system and in seemingly unrelated government policies. They may originate in other countries and transmit their effects through trade and the operation of transnational corporations. Underlying causes are many and operate in numerous and variable combinations. Forest decline is a complex socio-economic, cultural and political event. Thus, it is a mistake to attribute forest decline to a simple cause-effect relationship or assume that a relationship will remain unaltered over time. A single force, such as agricultural intensification, may operate in diametrically opposite ways, depending of the context of other variables and circumstances prevailing in a particular situation. Accordingly, remedial measures need to be tailored to the very specific milieu in which they will be introduced. There are no simple solutions to this complex phenomenon.